Si nanoparticles seeded in carbon-coated Sn nanowires as an anode for high-energy and high-rate lithium-ion batteries. (15th December 2021) - Ben, Liubin; Zhou, Jin; Ji, Hongxiang; Yu, Hailong; Zhao, Wenwu; Huang, Xuejie
Abstract: High-capacity and high-rate anode materials are desperately desired for applications in the next generation lithium-ion batteries. Here, we report preparation of an anode showing a structure of Si nanoparticles wrapped inside Sn nanowires. This anode inherits the advantages of both Si and Sn, endowing lithiation/delithiation of Si nanoparticles inside the conducting networks of Sn nanowires. It demonstrates a high and reversible capacity of ∼1500 mAh g −1 over 300 cycles at 0.2 °C and a good rate capability (0.2 °C–5 °C) equivalent to Sn. The excellent cycling performance is attributed to the novel structure of the anode as well as the strong mechanical strength of the nanowires which is directly confirmed by in-situ lithiation and bending experiments.